2024
DOI: 10.3390/jcs8040116
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Wheat Straw for the Production of Cement-Free Geopolymer Composite: Effects of Wheat Variety and Pre-Treatment Method

Regina Kalpokaitė-Dičkuvienė,
Inna Pitak,
Anastasiia Sholokhova
et al.

Abstract: The development of new composite materials with specific properties and reduced environmental pollution can be achieved by the incorporation of agricultural residues, whose morphology is strongly affected by their variety and growing conditions. Herein, the functional properties of a cement-free geopolymer composite reinforced with straw from two wheat varieties (Ada and Malibu) were investigated through different straw pre-treatment methods and their surface modification with silane coupling agents. The chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Meanwhile, the tensile strength and flexural strength of the composite material decreased with the increasing concentration of alkaline pretreatment [15]. Examining the influence of straw varieties on the properties of composite materials, the authors showed that the influence of straw varieties was not obvious [16]. In summary, the three factors of the straw dosage, pretreatment time, and concentration have the greatest impact on the composites.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, the tensile strength and flexural strength of the composite material decreased with the increasing concentration of alkaline pretreatment [15]. Examining the influence of straw varieties on the properties of composite materials, the authors showed that the influence of straw varieties was not obvious [16]. In summary, the three factors of the straw dosage, pretreatment time, and concentration have the greatest impact on the composites.…”
Section: Introductionmentioning
confidence: 98%
“…Many factors affect the thermal properties of composite materials, including the straw content, pretreatment time, sodium hydroxide concentration, straw variety, etc. Kammoun and Trabelsi studied the incorporation of straw into concrete, and concluded Sustainability 2024, 16, 5239 2 of 18 that the thermal conductivity and thermal diffusion coefficient decreased with the increase in the straw content [8,9]. Pachla researched the sound absorption performance and heat insulation performance of porous concrete when the straw content was 15% [10].…”
Section: Introductionmentioning
confidence: 99%